Electrolytic capacitor and manufacturing method

A carbon layer on the cathode foil in electrolytic capacitors addresses gas generation issues, enhancing capacitance and voltage withstand without nitro compounds, ensuring reliable operation for medium and high voltage applications.

JP7599433B2Active Publication Date: 2024-12-13NIPPON CHEMI CON CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021565617
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-18
Filing Date
2020-12-16
Publication Date
2024-12-13
Estimated Expiration
2040-12-16

AI Technical Summary

Technical Problem

Electrolytic capacitors for medium and high voltage applications face issues with gas generation due to the interaction between valve metal and water in the electrolyte, leading to potential bulging, leakage, and reduced capacitance, while adding gas absorbents like nitro compounds lowers withstand voltage.

Method used

Forming a carbon layer on the cathode foil of electrolytic capacitors to suppress gas generation, enhancing the capacitance appearance rate by increasing the cathode side capacitance, and using ethylene glycol as a solvent to improve withstand voltage.

Benefits of technology

The carbon layer on the cathode foil effectively reduces gas generation within the electrolytic capacitor, maintaining high withstand voltage without the need for nitro compounds, thus improving capacitance and preventing bulging or leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599433000005
    Figure 0007599433000005
  • Figure 0007599433000006
    Figure 0007599433000006
  • Figure 0007599433000007
    Figure 0007599433000007
Patent Text Reader

Abstract

Provided is an electrolytic capacitor for 100V or above medium / high voltage use, the capacitor being configured to suppress the total amount of gas generated inside the electrolytic capacitor. Anode foil of the electrolytic capacitor includes: a surface expansion part created by a tunnel-shaped pit formed in the direction of the foil depth from the foil surface; and a dielectric oxide film formed on the surface of the surface expansion part. A cathode body of the electrolytic capacitor includes a cathode foil made of a valve action metal, and a carbon layer formed on the cathode foil.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrolytic capacitor. and manufacturing method Regarding. [Background technology]

[0002] An electrolytic capacitor is a passive element that stores and discharges electric charge by electrostatic capacitance. An electrolytic capacitor is constructed by housing a capacitor element impregnated with an electrolytic solution in an exterior case, sealing the exterior case with a sealing body, and extending a lead terminal from the sealing body. The capacitor element is constructed by opposing an anode foil made of a valve metal foil with a dielectric oxide film formed thereon to a cathode foil made of the same or another metal foil, with a separator interposed between the anode foil and the cathode foil.

[0003] Electrolytic capacitors may be required to withstand voltages of 100V or more, such as for in-vehicle applications such as electric vehicles and power applications. Electrolytic capacitors that can withstand medium to high voltages of 100V or more require a thick dielectric oxide film. However, as the dielectric oxide film becomes thicker, the capacitance decreases. Therefore, electrolytic capacitors for medium to high voltage applications of 100V or more have a surface expansion layer made of a large number of tunnel-shaped pits on the anode foil. In addition, electrolytic capacitors have a surface expansion layer on the anode foil that has tunnel-shaped pits that penetrate the foil partially or entirely. In this way, by using surface expansion technology, electrolytic capacitors for medium to high voltage applications of 100V or more aim to increase the surface area of ​​the anode foil while ensuring the thickness of the dielectric oxide film. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2014-181368 A Summary of the Invention [Problem to be solved by the invention]

[0005] In electrolytic capacitors, gas is generated due to various phenomena. For example, on the anode side, when the dielectric oxide film dissolves and the moisture in the electrolyte comes into contact with the valve metal, hydrogen gas is generated due to hydration deterioration of the valve metal. Hydrogen gas is also generated at the foil interface on the cathode side. If the amount of gas generated in the electrolytic capacitor increases, it may cause the exterior case to swell, the valve to open, or the electrolyte to leak.

[0006] On the other hand, in recent years, electrolytic capacitors for medium to high voltage applications of 100V or more are required to have even higher capacitance. In other words, there is a demand to make the dielectric oxide film thinner while maintaining the withstand voltage. However, as the dielectric oxide film is made thinner, the valve metal becomes more likely to come into contact with the moisture in the electrolyte, which increases the chances of the valve metal reacting with the moisture in the electrolyte, resulting in a problem of increased hydrogen gas generation.

[0007] To cope with this problem, it has been considered to add gas absorbents or gas control agents such as nitro compounds to the electrolyte of electrolytic capacitors. However, nitro compounds tend to lower the withstand voltage of electrolytic capacitors, so it is desirable to reduce the amount of nitro compounds added for electrolytic capacitors that require medium to high voltages of 100V or more.

[0008] The present invention has been proposed to solve the above problems, and its object is to provide an electrolytic capacitor for medium to high voltage applications of 100 V or more, which suppresses the total amount of gas generated in the electrolytic capacitor. and manufacturing method The purpose of this invention is to provide [Means for solving the problem]

[0009] First, the capacitance appearance rate is defined. The capacitance appearance rate is the ratio of the capacitance of an electrolytic capacitor to the capacitance of the anode side. In other words, the capacitance appearance rate is the percentage obtained by dividing the composite capacitance, which is obtained by regarding the electrolytic capacitor as a capacitor in which the anode side and the cathode side are connected in series, by the anode side capacitance. The composite capacitance is obtained by dividing the product of the anode side capacitance and the cathode side capacitance by the sum of the anode side capacitance and the cathode side capacitance. Therefore, the capacitance appearance rate is expressed by the following formula 1.

[0010] (Formula 1) TIFF0007599433000001.tif16161

[0011] As shown in formula 1, when the capacitance of the anode side is large, the influence of the cathode side on the capacitance appearance rate becomes large. On the other hand, when the capacitance of the anode side is small, the influence of the cathode side on the capacitance appearance rate becomes small.

[0012] In the field of electrolytic capacitors, anode foils for electrolytic capacitors intended for so-called medium- and high-voltage applications (100V or more) have a smaller capacitance per unit area than anode foils for electrolytic capacitors intended for low-voltage applications. This is because the dielectric oxide film on the surface of the surface-expanded layer is thicker in anode foils for electrolytic capacitors intended for medium- and high-voltage applications in order to ensure the withstand voltage. From the viewpoint of improving the capacitance appearance rate, in electrolytic capacitors in the low-voltage range in which the capacitance on the anode side is large, it is very effective to increase the capacitance on the cathode side in order to increase the capacitance appearance rate. However, in electrolytic capacitors intended for medium- and high-voltage applications in which the capacitance on the anode side is small, the effect on the capacitance appearance rate is small even if the capacitance on the cathode side is increased.

[0013] For example, a 1cm electrolytic capacitor for low-voltage applications 2 When using an anode foil with a capacitance of 10 μF per cm 2 When a cathode foil with a capacitance of 100 μF per cm is used, the capacitance occurrence rate is 90.9%. 2 When the capacitance per cm is set to 1000 μF, the capacitance occurrence rate is 99.0%, which is an improvement of 109%. 2 For an anode foil with a capacitance of 1 μF per cm 2 When using a cathode foil with a capacitance of 100 μF per cm, the capacitance occurrence rate is 99.0%. 2 When the capacitance per unit is set to 1000 μF, the capacitance appearance rate is 99.9%, which is almost no improvement.

[0014] In electrolytic capacitors for medium to high voltage applications, where the effect on the capacitance appearance rate is small even if the capacitance on the cathode side is improved, the capacitance of the cathode foil has not been improved, taking into consideration the increase in the number of processes that would be required if a carbon material were used. However, as a result of intensive research by the present inventors, it was found that in electrolytic capacitors for medium to high voltage applications of 100V or more, the total amount of gas generated within the electrolytic capacitor is suppressed when a carbon layer is formed on the cathode foil.

[0015] The present invention was made based on this finding by the inventors, and the electrolytic capacitor of the present invention is an electrolytic capacitor comprising an anode foil and a cathode body, wherein the anode foil has an anode side expanded surface portion formed on a surface of the foil and a dielectric oxide film formed on the surface of the anode side expanded surface portion, and the cathode body has a cathode foil made of a valve metal and a carbon layer formed on the cathode foil.

[0016] The anode side expanded surface portion may have a tunnel-shaped pit formed from the foil surface in the foil thickness direction.

[0017] The cathode body may have an enlarged surface portion on a surface of the cathode foil, and the carbon layer may be formed on the cathode-side enlarged surface portion.

[0018] The carbon layer and the cathode side enlarged surface portion may be in pressure contact with each other.

[0019] The carbon layer may extend into the cathode side expanded surface portion.

[0020] The cathode side enlarged surface portion may be formed of spongy pits, and the carbon material of the carbon layer may penetrate into the spongy pits.

[0021] The battery may include an element formed of the anode foil and the cathode body, and an electrolyte filled in the element, the electrolyte being free of nitro-based compounds.

[0022] The cathode body may include an insulating layer formed on a surface of a foil, and the carbon layer may be formed on the insulating layer.

[0023] The insulating layer may be a natural oxide film or a chemical conversion film.

[0024] The battery may include an element formed of the anode foil and the cathode body, and an electrolyte filled in the element with a solvent containing ethylene glycol.

[0025] A part or all of the tunnel-shaped pits may extend through the anode foil.

[0026] It may be used for medium to high voltage applications of 100V or more. Effect of the Invention

[0027] According to the present invention, even in electrolytic capacitors for medium to high voltage applications of 100V or more, the amount of gas generated in the electrolytic capacitor can be suppressed. [Brief description of the drawings]

[0028] [Figure 1] 1 is a graph showing the amount of swelling of laminate cells of electrolytic capacitors of Examples 1 to 4 and Comparative Example 1. [Diagram 2] 1 is a graph showing the amount of swelling of laminate cells of electrolytic capacitors of Examples 5 to 13 and Comparative Example 2. [Diagram 3] 1 is a graph showing the amount of swelling of the exterior cases of the electrolytic capacitors of Examples 14 and 15 and Comparative Examples 3 and 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] The electrode body according to the embodiment of the present invention and an electrolytic capacitor using the electrode body as a cathode will be described. In this embodiment, an electrolytic capacitor having an electrolytic solution will be described as an example, but the present invention is not limited thereto. The present invention can be applied to any electrolytic capacitor using a gel electrolyte as an electrolyte.

[0030] (Electrolytic capacitor) An electrolytic capacitor is a passive device that stores and discharges electric charge according to its capacitance. This electrolytic capacitor has a wound or laminated capacitor element. The capacitor element is formed by placing an anode foil, on the surface of which a dielectric oxide film is formed, and a cathode body, which are opposed to each other via a separator, and are impregnated with an electrolyte. The electrolyte is in close contact with the uneven surface of the dielectric oxide film on the anode foil, and functions as a true cathode.

[0031] (cathode body) The cathode body has a cathode foil made of an elongated valve metal as a current collector. A natural oxide film or a chemical conversion film is formed on the surface of the cathode foil. The oxide film is formed naturally or intentionally. A natural oxide film is formed by the cathode foil reacting with oxygen in the air, while a chemical conversion film is an oxide film formed intentionally by a chemical conversion treatment in which a voltage is applied in a solution that does not contain halogen ions, such as an aqueous solution of adipic acid, boric acid, phosphoric acid, or the like. When the valve metal is aluminum foil, the oxide film is aluminum oxide.

[0032] A carbon layer containing carbon material as a main material is formed on the surface of this cathode foil. That is, the cathode body has an oxide film, which is an insulating layer, on the cathode foil, which is a current collector, and a carbon layer on this oxide film. The carbon layer is located on the outermost surface of the cathode body. When the carbon layer is located on the outermost surface of the cathode body, the total amount of gas generation in the electrolytic capacitor is suppressed. It is presumed that the total amount of gas generation in the electrolytic capacitor is suppressed due to a reduction in the amount of gas generation on the cathode side.

[0033] It is preferable that the carbon layer is in close contact with the cathode foil and is not easily peeled off from the cathode foil even when subjected to impact. If the carbon layer is not easily peeled off from the cathode foil, the total amount of gas generated in the electrolytic capacitor is further suppressed. In order to improve the adhesion between the carbon layer and the cathode foil, it is preferable to form a surface-expanding layer on the surface of the cathode foil and then form the carbon layer on the surface-expanding layer. In addition, in order to improve the adhesion between the carbon layer and the cathode foil, it is preferable to press the cathode body consisting of the carbon layer and the cathode foil.

[0034] The cathode body will be described in detail. The valve metal constituting the cathode foil is aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, antimony, etc. The purity is preferably about 99% or more, but impurities such as silicon, iron, copper, magnesium, zinc, etc. may be contained. For example, the cathode foil may be an aluminum material having a temper symbol H as specified by JIS standard H0001, so-called H material, or an aluminum material having a temper symbol O as specified by JIS standard H0001, so-called O material.

[0035] The surface-expanding layer is formed by electrolytic etching, chemical etching, sandblasting, or the like, or by depositing or sintering metal particles or the like on the foil. An example of electrolytic etching is AC etching. In AC etching, the cathode foil is immersed in an acidic aqueous solution containing halogen ions, such as hydrochloric acid, and an AC current is passed through it. In chemical etching, the metal foil is immersed in an acidic or alkaline solution. That is, the surface-expanding layer refers to a region where spongy etching pits are formed, or a region with a porous structure formed by gaps between dense powder particles. The etching pits may be tunnel-shaped pits formed by DC etching, or tunnel-shaped pits may be formed so as to penetrate the cathode foil.

[0036] The carbon material contained in the carbon layer is graphite, carbon black, or a mixture thereof. Examples of graphite include natural graphite, artificial graphite, graphitized ketjen black, etc. Examples of carbon black include ketjen black, acetylene black, channel black, and thermal black, etc.

[0037] The carbon material contained in the carbon layer is preferably carbon black, which is spherical carbon. When the surface-expanding layer formed on the surface of the cathode foil is an etching pit, the carbon black having a particle size smaller than the opening size of the etching pit is used, so that the carbon layer can easily penetrate deeper into the etching pit and the carbon layer can be tightly attached to the cathode foil.

[0038] The carbon material contained in the carbon layer may be flaky or scale-like graphite and carbon black, which is spherical carbon. The aspect ratio of the minor axis to the major axis of the flaky or scale-like graphite is preferably in the range of 1:5 to 1:100. The carbon black, which is spherical carbon, preferably has an average primary particle size of 100 nm or less. When a carbon layer containing this combination of carbon materials is laminated on a cathode foil, the carbon black is easily rubbed into the pores of the surface-expanding layer by the graphite. The graphite is easily deformed along the uneven surface of the surface-expanding layer and is easily piled up on the uneven surface. The graphite acts as a pressing lid to hold down the spherical carbon rubbed into the pores. Therefore, the adhesion and fixation between the carbon layer and the cathode foil are further improved.

[0039] In addition, the carbon layer may contain activated carbon, carbon nanohorns, or fibrous carbon as the carbon material. Activated carbon is made from natural plant tissue such as coconut shells, synthetic resins such as phenol, and fossil fuels such as coal, coke, and pitch. Examples of fibrous carbon include carbon nanotubes (hereinafter, CNTs) and carbon nanofibers (hereinafter, CNFs). Activated carbon and fibrous carbon are preferable because they have delocalized pi electrons and a large specific surface area.

[0040] Methods for forming a carbon layer on a cathode foil include vacuum deposition, sputtering, ion plating, CVD, coating, electrolytic plating, and electroless plating. In the coating method, a carbon material is dispersed in a dispersion solvent to prepare a slurry, and the slurry is coated on the cathode foil by a slurry casting method, a doctor blade method, a spray atomization method, or the like, and dried. In the deposition method, the carbon material is evaporated by applying an electric current to heat the carbon material in a vacuum, or evaporated by applying an electron beam to the carbon material in a vacuum, and a film of the carbon material is formed on the cathode foil. In addition, in the sputtering method, a target made of a carbon material and the cathode foil are placed in a vacuum container, and an inert gas is introduced into the vacuum container and a voltage is applied to cause the plasmatized inert gas to collide with the target, and the particles of the carbon material knocked out from the target are deposited on the cathode foil.

[0041] After laminating the carbon layer and the cathode foil, it is preferable to press them together. In the press process, for example, the cathode body consisting of the carbon layer and the cathode foil is sandwiched between press rollers and a linear press pressure is applied. The press pressure is 0.01 to 100 t / cm. 2 As long as the carbon layer and the cathode foil can be pressed together, there is no particular limitation on the pressed structure formed at the interface of the cathode foil, but if a carbon material is forced into the pores of the surface-expanded layer by pressing and the carbon material is deformed along the uneven surface of the surface-expanded layer, the adhesion and fixation between the carbon layer and the cathode body can be further improved. In particular, carbon black, which is a spherical carbon, is rubbed into the pores of the surface-expanded layer by graphite under pressure, and the graphite is easily deformed and piled up along the uneven surface of the surface-expanded layer.

[0042] Carbon materials such as graphite and carbon black may also be subjected to a porous treatment such as an activation treatment or an opening treatment. As the porous treatment, a conventionally known activation treatment such as a gas activation method or a chemical activation method can be used. Examples of the gas used in the gas activation method include water vapor, air, carbon monoxide, carbon dioxide, hydrogen chloride, oxygen, or a gas consisting of a mixture of these. Examples of the chemicals used in the chemical activation method include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkaline earth metal hydroxides such as calcium hydroxide, inorganic acids such as boric acid, phosphoric acid, sulfuric acid, and hydrochloric acid, and inorganic salts such as zinc chloride. During this activation treatment, a heat treatment is performed as necessary.

[0043] (anode foil) The anode foil is a long foil made of valve metal. The purity of the anode foil is preferably about 99.9% or more. This anode foil is formed by forming a surface expansion layer on a stretched foil and forming a dielectric oxide film on the surface of the surface expansion layer. The surface expansion layer is suitable for medium to high voltage applications of 100V or more, and has many tunnel-shaped pits dug in the thickness direction from the foil surface by direct current etching. To accommodate high capacity in medium to high voltage applications of 100V or more, the tunnel-shaped pits may be formed so as to penetrate the anode foil. Alternatively, the surface expansion layer is formed by sintering valve metal powder, or by depositing a film of metal particles or the like on the foil to apply a film.

[0044] The dielectric oxide film formed on the anode foil is typically an oxide film formed on the surface layer of the anode foil, and if the anode foil is made of aluminum, it is an aluminum oxide layer formed by oxidizing the porous structure region. This dielectric oxide film is formed by chemical conversion treatment in which a voltage is applied in a solution that does not contain halogen ions, such as an acid such as ammonium borate, ammonium phosphate, or ammonium adipate, or an aqueous solution of such an acid.

[0045] (electrolyte) The solvent of the electrolyte is preferably ethylene glycol. When ethylene glycol is used as the solvent, the withstand voltage of the electrolytic capacitor is improved, making it suitable for medium to high voltage applications of 100V or more. However, as long as the required withstand voltage can be obtained by surface expansion treatment and chemical conversion treatment of the anode foil, the solvent may be either a protic polar solvent or an aprotic polar solvent. Representative examples of protic polar solvents include monohydric alcohols, polyhydric alcohols, oxyalcohol compounds, water, and the like. Representative examples of aprotic polar solvents include sulfones, amides, lactones, cyclic amides, nitriles, oxides, and the like.

[0046] Examples of monohydric alcohols include ethanol, propanol, butanol, pentanol, hexanol, cyclobutanol, cyclopentanol, cyclohexanol, and benzyl alcohol. Examples of polyhydric alcohols and oxyalcohol compounds include ethylene glycol, propylene glycol, glycerin, methyl cellosolve, ethyl cellosolve, methoxypropylene glycol, and dimethoxypropanol. Examples of sulfones include dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, sulfolane, 3-methyl sulfolane, and 2,4-dimethyl sulfolane. Examples of amides include N-methylformamide, N,N-dimethylformamide, N-ethylformamide, N,N-diethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-ethylacetamide, N,N-diethylacetamide, and hexamethylphosphoric amide. Examples of lactones and cyclic amides include γ-butyrolactone, γ-valerolactone, δ-valerolactone, N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butylene carbonate, and isobutylene carbonate. Examples of nitriles include acetonitrile, 3-methoxypropionitrile, and glutaronitrile. Examples of oxides include dimethyl sulfoxide. As the solvent, these may be used alone or in combination of two or more.

[0047] The solute contained in the electrolytic solution includes anion and cation components, and is typically an organic acid or its salt, an inorganic acid or its salt, or a composite compound of an organic acid and an inorganic acid or its ion-dissociable salt, and is used alone or in combination of two or more. An acid that becomes an anion and a base that becomes a cation may be added separately to the electrolytic solution as solute components.

[0048] Examples of organic acids that become anion components in the electrolyte include carboxylic acids such as oxalic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, adipic acid, benzoic acid, toluic acid, enanthic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, undecanediacid, dodecanediacid, and tridecanediacid, phenols, and sulfonic acids. Examples of inorganic acids include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid. Examples of composite compounds of organic and inorganic acids include borodisalicylic acid, borodioxalic acid, and borodiglycolic acid.

[0049] In addition, examples of at least one salt of an organic acid, an inorganic acid, and a complex compound of an organic acid and an inorganic acid include ammonium salt, quaternary ammonium salt, quaternary amidinium salt, amine salt, sodium salt, potassium salt, etc. Examples of the quaternary ammonium ion of the quaternary ammonium salt include tetramethylammonium, triethylmethylammonium, tetraethylammonium, etc. Examples of the quaternary amidinium include ethyldimethylimidazolinium, tetramethylimidazolinium, etc. Examples of the amine of the amine salt include primary amine, secondary amine, and tertiary amine. Examples of the primary amine include methylamine, ethylamine, propylamine, etc., examples of the secondary amine include dimethylamine, diethylamine, ethylmethylamine, dibutylamine, etc., and examples of the tertiary amine include trimethylamine, triethylamine, tributylamine, ethyldimethylamine, ethyldiisopropylamine, etc.

[0050] Furthermore, other additives may be added to the electrolytic solution, such as phosphoric acid, phosphoric acid esters, and other phosphoric acid compounds, boric acid, boric acid esters, and other boric acid compounds, complexes of boric acid with sugar alcohols such as mannitol and sorbitol, polyoxyalkylene polyols such as polyethylene glycol, polyglycerin, and polypropylene glycol, and colloidal silica, which improve the withstand voltage of the electrolytic capacitor.

[0051] The additive may also include a nitro compound. Examples of the nitro compound include o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, p-nitrophenol, p-nitrobenzene, o-nitrophenol, m-nitrophenol, and p-nitrophenol. The nitro compound has a hydrogen gas absorbing effect. However, the nitro compound reduces the withstand voltage. On the other hand, the total amount of gas generated in the electrolytic capacitor is suppressed by forming a carbon layer on the cathode foil. Therefore, in order to meet medium and high voltage applications of 100V or more, it is preferable to reduce the amount of nitro compound added as much as possible, and it is more preferable to not include the nitro compound.

[0052] (Separator) The separator is interposed between the anode foil and the cathode body to prevent short circuit between the anode foil and the cathode body, and also holds the electrolyte. Examples of the separator include cellulose and mixed papers such as kraft, Manila hemp, esparto, hemp, and rayon, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof, polytetrafluoroethylene resins, polyvinylidene fluoride resins, vinylon resins, polyamide resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides, polyimide resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, and acrylic resins. These resins can be used alone or in combination, or can be used in combination with cellulose. In addition, if the electrolyte has shape retention and the thickness of the electrolyte is maintained, the separator may be omitted.

[0053] (Example) The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0054] (Examples 1 to 4) Example 1 The electrolytic capacitor of Example 1 was produced. Aluminum foil was used as the cathode foil. The aluminum foil was subjected to an AC etching treatment, and a surface-enlarging layer consisting of spongy etching pits was formed on both sides of the foil. In the AC etching treatment, the cathode foil was immersed in an acidic aqueous solution containing about 8% by weight of hydrochloric acid as the main electrolyte at a liquid temperature of 25°C, and an AC of 10 Hz and a current density of 0.14 A / cm was applied. 2 A current of this magnitude was applied to the substrate for approximately 5 minutes to enlarge the surface area of ​​both sides of the aluminum foil.

[0055] Next, the aluminum foil was subjected to a chemical conversion treatment to form an oxide film on the surface of the surface-expanding layer. In the chemical conversion treatment, chlorine that had adhered during the AC etching treatment was removed using an aqueous phosphoric acid solution, and then a voltage was applied in an aqueous solution of ammonium dihydrogen phosphate.

[0056] First, graphite and carbon black were added to the carbon layer of the cathode body as carbon materials. Graphite (G) and carbon black (C) were added to the carbon layer at a weight ratio of G:C = 75:25. Specifically, graphite powder, carbon black powder, styrene butadiene rubber (SBR) as a binder, and a carboxymethylcellulose sodium (CMC-Na) aqueous solution as a dispersant-containing aqueous solution were mixed and kneaded to prepare a slurry.

[0057] This slurry was applied uniformly to the cathode foil. The slurry was then heated and dried to volatilize the solvent, after which the cathode body was pressed. In the press process, the cathode body was sandwiched between press rollers and pressed with a pressure of 5.38 kNcm. -1 The carbon layer was fixed onto the cathode foil by applying a linear pressure of 180 mm. The linear pressure was applied using a press machine manufactured by Takumi Giken Co., Ltd. The diameter of the press roller was 180 mm, the width of the press treatment was 130 mm, and the cathode body was transported once at 3 m / min.

[0058] In addition, aluminum foil was used as the anode foil. The aluminum foil was subjected to a DC etching process to form a surface-expanding layer consisting of tunnel-shaped etching pits. The DC etching process used a first process to form pits and a second process to expand the pits. In the first process, the aluminum foil was electrochemically etched with a DC current in an aqueous solution containing chloride ions. The etching process in the first process was performed with a current density of 400 mA / cm. 2 In the second step, in order to enlarge the pits formed in the aluminum foil after the first step, electrochemical etching was performed with a direct current in an aqueous solution containing nitrate ions. The current density of the etching in the second step was 300 mA / cm. 2 This was done for about 2 minutes.

[0059] After forming the surface-expanding layer, the anode foil was subjected to chemical conversion treatment to form a dielectric oxide film on the surface of the surface-expanding layer. Specifically, a voltage of 286 V was applied in a chemical conversion solution of 4% by weight of boric acid at a liquid temperature of 85°C.

[0060] An aluminum tab-shaped lead-out terminal was ultrasonically connected to the anode foil and the cathode body. A separator folded in zigzag was prepared, and the cathode body and the anode foil were alternately sandwiched between the folds to create a laminate of the cathode body, the anode foil, and the separator, with the cathode body and the anode foil facing each other with the separator interposed between them. A craft separator was used as the separator.

[0061] The laminate was impregnated with an electrolytic solution. The electrolytic solution contained ethylene glycol as a solvent and azelaic acid salt as a solute. No nitro compound was added to the electrolytic solution. After impregnation with the electrolytic solution, the laminate was sealed in a laminate material. In this way, an electrolytic capacitor of a laminate cell was produced. The laminate material was made of aluminum with a thickness of 110 μm. After the laminate cell was produced, an aging treatment was performed. In the aging treatment, a voltage of 230 V was applied to the laminate cell for 120 minutes at room temperature (25° C.), and then a voltage of 230 V was applied for 60 minutes in a temperature environment of 85° C.

[0062] Example 2 An electrolytic capacitor of Example 2 was produced. In the electrolytic capacitor of Example 2, the cathode foil was not subjected to AC etching treatment, and no surface-enlarging layer was formed on the cathode foil. Other than that, the electrolytic capacitor of Example 2 was produced by the same method and under the same conditions as Example 1, including the composition of the carbon layer formed on the cathode foil, the press processing of the cathode body, and the fact that no nitro compound was added.

[0063] Example 3 An electrolytic capacitor of Example 3 was produced. In the electrolytic capacitor of Example 3, press processing was not performed in the process of forming a carbon layer on the cathode foil. Other than that, the electrolytic capacitor of Example 3 was produced by the same method and under the same conditions as Example 1, including the formation of a surface-enlarging layer by AC etching on the cathode foil, the composition of the carbon layer formed on the cathode foil, and the fact that a nitro compound was not added.

[0064] Example 4 An electrolytic capacitor of Example 4 was produced. In the electrolytic capacitor of Example 4, a cathode body on which a carbon layer was formed by a sputtering method was used. A surface-expanding layer was formed on the cathode foil, and a natural oxide film was formed as an oxide film. In the process of forming the carbon layer, press processing was not performed. In addition, the electrolytic capacitor of Example 4 was produced by the same method and under the same conditions as Example 1, including the formation of the surface-expanding layer by AC etching treatment on the cathode foil and the fact that no nitro compound was added.

[0065] Comparative Example 1 An electrolytic capacitor of Comparative Example 1 was produced. In the electrolytic capacitor of Comparative Example 1, a surface-expanding layer was formed on the cathode foil, but a carbon layer was not formed. Other than that, including the fact that no nitro compound was added, the electrolytic capacitor of Comparative Example 1 was produced by the same method and under the same conditions as Example 1.

[0066] (Gas generation measurement test) The amount of gas generated was measured for the electrolytic capacitors of Examples 1 to 4 and Comparative Example 1. A voltage of DC 219V was continuously applied to each electrolytic capacitor in a temperature environment of 105°C, and the amount of gas generated after 392 hours was measured. The amount of gas generated was measured based on the amount of swelling of the laminate cell. The amount of swelling of the laminate cell was measured by the Archimedes method. That is, the laminate cell was immersed in water and the weight increase was measured to measure the volume of liquid displaced by the laminate cell.

[0067] The measurement results of the amount of gas generated are shown in Table 1 below. In Table 1 below, the differences between the cathode bodies of Examples 1 to 4 and Comparative Example 1 are also shown. In addition, the graph of Fig. 1 was created based on Table 1. Fig. 1 is a graph showing the amount of bulging in Examples 1 to 4 and Comparative Example 1. (Table 1) TIFF0007599433000002.tif71161

[0068] As shown in Table 1 and FIG. 1, the swelling amount of the electrolytic capacitor of Comparative Example 1 was 3 cm 3 In contrast, the swelling amount of the electrolytic capacitors of Examples 1 to 4 was at most 2.5 cm3 As shown in Table 1, in Comparative Example 1, the carbon layer was not laminated on the cathode foil, whereas in Examples 1 to 4, the carbon layer was laminated on the cathode foil. Therefore, it was confirmed that the total amount of gas generation in the electrolytic capacitor was suppressed by laminating a carbon layer on the cathode foil.

[0069] As shown in Table 1 and FIG. 1, the swelling amount of the electrolytic capacitor of Example 2 was 2.5 cm 3 The maximum swelling amount of the electrolytic capacitors of Examples 1, 3 and 4 was 2.1 cm 3 As shown in Table 1, in Example 2, the cathode foil does not have a surface-expanding layer formed thereon, whereas in Examples 1, 3, and 4, the cathode foil has a surface-expanding layer formed thereon. Therefore, it was confirmed that the total amount of gas generation in the electrolytic capacitor is further suppressed by forming a surface-expanding layer and a carbon layer on the cathode foil.

[0070] As shown in Table 1 and FIG. 1, the swelling of the electrolytic capacitor of Example 1 was 2 cm 3 As shown in Table 1, in Examples 3 and 4, the press working was omitted when forming the carbon layer on the cathode foil, whereas in Example 1, the press working was applied when forming the carbon layer on the cathode foil. Therefore, it was confirmed that the total amount of gas generation in the electrolytic capacitor was further suppressed by forming a surface expansion layer and a carbon layer on the cathode foil and adding the press working when forming the carbon layer.

[0071] (Examples 5 to 13) Example 5 An electrolytic capacitor of Example 5 was produced. The electrolytic capacitor of Example 5 was produced by the same method and under the same conditions as Example 1, except for the voltage of the chemical conversion treatment and the voltage of the aging. In Example 5, the voltage during the chemical conversion treatment of the anode foil was increased compared to Example 1, and a voltage of 534 V was applied to perform the chemical conversion treatment. In Example 5, the voltage during aging was increased compared to Example 1, and a voltage of 450 V was applied to the laminate cell at room temperature for 120 minutes, and then a voltage of 425 V was applied for 60 minutes in a temperature environment of 85 degrees Celsius.

[0072] Example 6 The electrolytic capacitor of Example 6 was produced. The electrolytic capacitor of Example 6 was produced by the same method and under the same conditions as Example 2, except for the voltage of the chemical conversion treatment of the anode foil and the voltage of the aging. The voltage of the chemical conversion treatment of the anode foil and the voltage of the aging were the same as those of Example 5.

[0073] Example 7 The electrolytic capacitor of Example 7 was produced. The electrolytic capacitor of Example 7 was produced by the same method and under the same conditions as Example 3, except for the voltage of the chemical conversion treatment of the anode foil and the voltage of the aging. The voltage of the chemical conversion treatment of the anode foil and the voltage of the aging were the same as those of Example 5.

[0074] Example 8 An electrolytic capacitor of Example 8 was produced. In the electrolytic capacitor of Example 8, no AC etching was performed on the cathode foil, and no surface enlargement layer was formed on the cathode foil. In addition, press processing was not performed in the process of forming a carbon layer on the cathode foil. Other than that, including the composition of the carbon layer formed on the cathode foil and the fact that no nitro compound was added, the electrolytic capacitor of Example 8 was produced by the same method and under the same conditions as Example 1. However, the voltage of the chemical conversion treatment and the voltage of the aging of the anode foil were the same as those of Example 5.

[0075] Example 9 An electrolytic capacitor of Example 9 was produced. The carbon layer of the electrolytic capacitor of Example 9 contained only carbon black as the carbon material. Specifically, a slurry was produced by mixing and kneading carbon black powder, styrene butadiene rubber (SBR) as a binder, and a carboxymethyl cellulose sodium (CMC-Na) aqueous solution as a dispersant-containing aqueous solution. In addition, the electrolytic capacitor of Example 9 was produced by the same method and under the same conditions as Example 1, including the formation of a surface-enlarging layer by AC etching treatment on the cathode foil, the press processing of the cathode body, and the fact that no nitro compound was added. However, the voltage of the chemical conversion treatment and the voltage of the aging of the anode foil were the same as those of Example 5.

[0076] Example 10 An electrolytic capacitor of Example 10 was produced. In the electrolytic capacitor of Example 10, press processing was not performed in the process of forming a carbon layer on the cathode foil. Other than that, the electrolytic capacitor of Example 10 was produced by the same method and under the same conditions as Example 9, including the formation of a surface-enlarging layer by AC etching treatment on the cathode foil, the composition of the carbon layer formed on the cathode foil, and the fact that no nitro compound was added. The voltage of the chemical conversion treatment and the aging voltage of the anode foil were the same as those of Example 5.

[0077] Example 11 An electrolytic capacitor of Example 11 was produced. In the electrolytic capacitor of Example 11, AC etching was not performed on the cathode foil, and a surface expansion layer was not formed on the cathode foil. In addition, press processing was not performed in the process of forming a carbon layer on the cathode foil. Other than that, including the composition of the carbon layer formed on the cathode foil and the fact that a nitro compound was not added, the electrolytic capacitor of Example 11 was produced by the same method and under the same conditions as Example 9. However, the voltage of the chemical conversion treatment and the voltage of the aging of the anode foil were the same as those of Example 5.

[0078] Example 12 The electrolytic capacitor of Example 12 was produced. The electrolytic capacitor of Example 12 was produced by the same method and under the same conditions as Example 4, except for the voltage of the chemical conversion treatment and the voltage of the aging. The voltage of the chemical conversion treatment and the voltage of the aging of the anode foil were the same as those of Example 5.

[0079] (Example 13) An electrolytic capacitor of Example 13 was produced. In the electrolytic capacitor of Example 13, AC etching was not performed on the cathode foil, and a surface expansion layer was not formed on the cathode foil. In addition, press processing was not performed in the process of forming a carbon layer on the cathode foil. Other than that, including the fact that no nitro compound was added, the electrolytic capacitor of Example 13 was produced by the same method and under the same conditions as Example 12. The voltage of the chemical conversion treatment and the voltage of the aging of the anode foil were the same as those of Example 5.

[0080] Comparative Example 2 An electrolytic capacitor of Comparative Example 2 was produced. The electrolytic capacitor of Comparative Example 2 was produced by the same method and under the same conditions as Comparative Example 1, except for the voltage of the chemical conversion treatment and the voltage of the aging. The voltage of the chemical conversion treatment and the voltage of the aging of the anode foil were the same as those of Example 5.

[0081] (Gas generation measurement test) The amount of gas generated was measured for the electrolytic capacitors of Examples 5 to 13 and Comparative Example 2. The method and conditions for measuring the amount of gas generated were the same as those for Examples 1 to 4 and Comparative Example 1, except for the applied voltage and the timing of measuring the amount of swelling. That is, for the electrolytic capacitors of Examples 5 to 13 and Comparative Example 2, a voltage of DC 409 V was continuously applied in a temperature environment of 105° C., and the amount of gas generated after 232 hours was measured.

[0082] The measurement results of the amount of gas generated are shown in Table 2 below. Three samples were prepared for each Example and Comparative Example, and the average value of the three samples was used as the measurement result. Table 2 below also shows the differences in the cathode bodies of Examples 5 to 13 and Comparative Example 2. In addition, the graph of FIG. 2 was created based on Table 2. FIG. 2 is a graph showing the amount of swelling of Examples 5 to 13 and Comparative Example 2. (Table 2) TIFF0007599433000003.tif121161

[0083] As shown in Table 2 and FIG. 2, the swelling amount of the electrolytic capacitor of Comparative Example 2 was 1.5 cm 3 In contrast, the swelling amount of the electrolytic capacitors of Examples 5 to 13 was at most 1.01 cm 3 As shown in Table 2, in Comparative Example 2, no carbon layer was laminated on the cathode foil, whereas in Examples 5 to 13, a carbon layer was laminated on the cathode foil. Therefore, it was confirmed from the results of Examples 5 to 13 and Comparative Example 2 that the total amount of gas generation in the electrolytic capacitor was suppressed when a carbon layer was laminated on the cathode foil.

[0084] In Table 2 and FIG. 2, electrolytic capacitors of Examples 5 to 8 having the same carbon layer are compared. Example 6, in which pressing is performed, has a suppressed amount of swelling compared to Example 8, in which the surface-expanding layer is not formed and pressing is not performed. Example 7, in which the surface-expanding layer is formed, has a suppressed amount of swelling compared to Example 8, in which the surface-expanding layer is not formed and pressing is not performed. Furthermore, Example 5, in which the surface-expanding layer is formed and pressing is performed, has a better amount of swelling compared to any of Examples 6 to 8. In addition, electrolytic capacitors of Examples 9 to 11, in which the carbon layer contains only carbon black as a carbon material, are compared. Example 9, in which pressing is performed, has a suppressed amount of swelling compared to Examples 10 and 11, in which pressing is not performed.

[0085] As a result, the results of Examples 5 to 13 and Comparative Example 2 confirmed that when a surface expansion layer and a carbon layer are formed on the cathode foil, or when a carbon layer is formed on the cathode foil and then press-processed, the total amount of gas generation in the electrolytic capacitor tends to be further suppressed.

[0086] 2, comparing Example 7 and Example 10, which differ only in the configuration of the carbon layer, the amount of swelling is suppressed in Example 7, in which graphite is mixed into the carbon layer. In other words, it was confirmed that the total amount of gas generation in the electrolytic capacitor is further suppressed by selecting graphite in addition to carbon black as the carbon material to be contained in the carbon layer.

[0087] Example 14 Further, an electrolytic capacitor of Example 14 was produced. In contrast to Example 1, in which the capacitor element was sealed in a laminate material, the electrolytic capacitor of Example 14 was inserted into an aluminum exterior case and sealed with a sealing body. The exterior case was a cylindrical bottomed tube with a side thickness of 0.4 mm. The conditions of the chemical conversion treatment of the anode foil were different from those of Example 1, and in Example 14, a voltage of 650 V was applied in a chemical conversion solution of 4 wt % boric acid at a liquid temperature of 85° C. In addition, the conditions of the aging treatment were different from those of Example 1, and in Example 14, a voltage of 481 V was applied for 95 minutes at room temperature (30° C.). In addition, the electrolytic capacitor of Example 14 was produced by the same method and under the same conditions as Example 1, including the composition of the carbon layer formed on the cathode foil, the press processing of the cathode body, and the fact that a nitro compound was not added.

[0088] Example 15 An electrolytic capacitor of Example 15 was produced. The electrolytic capacitor of Example 15 differs from the electrolytic capacitor of Example 14 in the presence or absence of a nitro compound in the electrolytic solution. In the electrolytic capacitor of Example 15, paranitrobenzyl alcohol was added as a nitro compound to the electrolytic solution. The amount of the nitro compound added was 2% by weight. Other than that, the electrolytic capacitor of Example 15 was produced by the same method and under the same conditions as Example 14, including the composition of the carbon layer formed on the cathode foil and the press processing of the cathode body.

[0089] Comparative Example 3 An electrolytic capacitor of Comparative Example 3 was produced. In the electrolytic capacitor of Comparative Example 3, a carbon layer was not formed on the cathode body. Other than that, including the point that a nitro compound was not added, the electrolytic capacitor of Comparative Example 3 was produced by the same method and under the same conditions as those of Example 13.

[0090] Comparative Example 4 An electrolytic capacitor of Comparative Example 4 was produced. In the electrolytic capacitor of Comparative Example 4, no carbon layer was formed on the cathode body. However, in the electrolytic capacitor of Comparative Example 4, paranitrobenzyl alcohol was added as a nitro compound to the electrolytic solution. The amount of the nitro compound added was 2% by weight. Otherwise, the electrolytic capacitor of Comparative Example 4 was produced by the same method and under the same conditions as Comparative Example 3.

[0091] (Gas generation measurement test) The amount of gas generated was measured for the electrolytic capacitors of Examples 14 and 15 and Comparative Examples 3 and 4. A voltage of DC 450 V was continuously applied to each electrolytic capacitor in a temperature environment of 105° C., and the amount of gas generated was measured at each time up to 3000 hours after the start of the test. The amount of gas generated was measured by visually measuring the change in radius of the measurement location at the maximum expansion point of the outer case.

[0092] The measurement results of the amount of gas generated are shown in Figure 3. In Figure 3, black diamonds indicate Example 14, black circles indicate Example 15, white circles indicate Comparative Example 3, and white diamonds indicate Comparative Example 4. Figure 3 is a graph showing the amount of swelling of the exterior case over time, with the horizontal axis representing the elapsed time and the vertical axis representing the amount of swelling for Examples 14 and 15 and Comparative Examples 3 and 4. The differences in the cathode bodies of Examples 14 and 15 and Comparative Examples 3 and 4 are summarized in Table 3 below. As shown in Table 3, the difference between Examples 14 and 15 and Comparative Examples 3 and 4 is the presence or absence of a carbon layer, and the difference between Example 14 and Example 15 is the presence or absence of the addition of a nitro compound.

[0093] (Table 3) TIFF0007599433000004.tif61141

[0094] As shown in Table 3 and FIG. 3, in Comparative Example 4 in which a nitro compound was added to the electrolyte, the time required for the swelling amount of the outer case to reach 1.5 mm, which is the swelling limit, was longer than in Comparative Example 3 in which a nitro compound was not added. In other words, it can be confirmed that the nitro compound suppresses the amount of gas generation. However, the swelling amount of the electrolytic capacitor in Comparative Example 4 also reached the swelling limit of the outer case after about 1500 hours. On the other hand, as shown in Table 3 and FIG. 3, in Examples 14 and 15 in which a carbon layer was formed by pressing a cathode foil having a surface expansion layer, the swelling of the outer case was kept low and the swelling amount did not reach the limit.

[0095] Moreover, as can be seen from a comparison between Examples 14 and 15, the degree of swelling of the exterior case did not change significantly depending on whether or not a nitro compound was present. The electrolytic capacitor of Example 5 does not contain a nitro compound in the electrolyte, while the electrolytic capacitor of Example 15 contains a nitro compound in the electrolyte. In other words, it was confirmed that if a carbon layer is laminated on the electrode foil, the total amount of gas generated in the electrolytic capacitor can be suppressed, and therefore it is possible to eliminate the inclusion of a nitro compound, which is a gas absorbent. This also improves the withstand voltage of the electrolytic capacitor.

Claims

1. An electrolytic capacitor used for medium to high voltage applications of 100 V or more, comprising an anode foil and a cathode body, The anode foil is an anode-side enlarged surface portion formed on the foil surface; a dielectric oxide film formed on the surface of the anode side expanded surface portion; having the anode-side expanded surface portion has a tunnel-shaped pit formed from a foil surface in a foil thickness direction, The cathode body is a cathode foil made of a valve metal; A cathode side enlarged surface portion formed on a surface of the cathode foil; a carbon layer formed on the cathode side expanded surface portion and penetrating into the cathode side expanded surface portion; having the carbon layer and the cathode side enlarged surface portion are pressure-welded together; An electrolytic capacitor characterized by:

2. The cathode body has an effect of suppressing the amount of hydrogen gas generated; 2. The electrolytic capacitor according to claim 1 .

3. The cathode side enlarged surface portion is formed of spongy pits, the carbon material of the carbon layer penetrates into the spongy pits; 2. The electrolytic capacitor according to claim 1 .

4. An element consisting of the anode foil and the cathode body; an electrolyte filled in the element; Equipped with The electrolyte does not contain a nitro compound; 4. The electrolytic capacitor according to claim 1, wherein

5. The cathode body has an insulating layer formed on a foil surface, the carbon layer is formed on the insulating layer; 5. The electrolytic capacitor according to claim 1,

6. The insulating layer is a natural oxide film or a chemical conversion film; 6. The electrolytic capacitor according to claim 5 .

7. An element consisting of the anode foil and the cathode body; an electrolyte filled in the element, the electrolyte being a solvent containing ethylene glycol; To have 7. The electrolytic capacitor according to claim 1,

8. a part or all of the tunnel-shaped pit penetrates the anode foil; 8. The electrolytic capacitor according to claim 1,

9. A method for manufacturing an electrolytic capacitor used for medium to high voltage applications of 100 V or more, the electrolytic capacitor including an anode foil and a cathode body, comprising: forming an anode-side expanded surface portion on a foil surface of the anode foil, the anode foil having a tunnel-shaped pit formed from the foil surface in a foil thickness direction; forming a dielectric oxide film on a surface of the anode side expanded surface portion; forming a cathode side enlarged surface portion on a surface of a cathode foil made of a valve metal; forming a carbon layer on the cathode side expanded surface portion; pressing the carbon layer against the cathode side expanded surface portion to cause the carbon layer to penetrate into the cathode side expanded surface portion; having A method for manufacturing an electrolytic capacitor comprising the steps of:

Citation Information

Patent Citations

  • Aluminum electrolytic capacitor and method of manufacturing same

    JP1980021101A

  • Aluminum electrolytic capacitor and its manufacturing method

    JP2006080111A

  • Electrolyte capacitor and manufacturing method thereof

    JP2006190878A

  • Aluminum alloy foil for electrolytic capacitor and production method thereof

    JP2014181368A

  • Electrolytic capacitor

    WO2019194092A1